2020
DOI: 10.3390/met10101313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of True Strains in Isothermal abc Pressing on Mechanical Properties of Ti49.8Ni50.2 Alloy

Abstract: The paper analyzes the microstructure and mechanical properties of Ti49.8Ni50.2 alloy (at.%) under uniaxial tension at room temperature after isothermal abc pressing to true strains e = 0.29−8.44 at T = 723 K. The analysis shows that as the true strain e is increased, the grain–subgrain structure of the alloy is gradually refined. This leads to an increase in its yield stress σy and strain hardening coefficient θ = dσ/dε at linear stage III of its tensile stress–strain curve according to the Hall–Petch relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
9
1
3
Order By: Relevance
“…The test material was Ti 49.8 Ni 50.2 (at%) supplied by MATEK-SMA Ltd. (Moscow, Russia). Its specimens were made as described in detail elsewhere [22]. The initial specimens, which were shaped as a cube with a side of 20 mm via a single abc pressing cycle at 1073 K, were placed in dies, aged at 573 K for 10 min, and compressed on a hydraulic press with a rate of 0.16-0.18 s −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test material was Ti 49.8 Ni 50.2 (at%) supplied by MATEK-SMA Ltd. (Moscow, Russia). Its specimens were made as described in detail elsewhere [22]. The initial specimens, which were shaped as a cube with a side of 20 mm via a single abc pressing cycle at 1073 K, were placed in dies, aged at 573 K for 10 min, and compressed on a hydraulic press with a rate of 0.16-0.18 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…After abc pressing to e = 8.44 at 723 K [19][20][21][22], this type of alloy acquires an inhomogeneous grain-subgrain structure with an average grain size of approximately 1 µm that comprises fine-grained, submicrocrystalline, and nanocrystalline fractions. It is noted that intense recovery processes develop in the alloy abc pressed at 723 K.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that in the temperature range studied, the maximum inelastic strain that could be obtained in the coarse-grained samples subjected to torsion could be completely returned due to the superelasticity effect of 4-7%. The effect of true strains on the microstructure and mechanical properties of a Ti 49.8 Ni 50.2 alloy subjected to isothermal abc pressing was analysed in [3]. It was shown that the grain structure of the alloy was refined by increasing the true strain, which increased its yield stress and strain-hardening coefficient.…”
Section: Contributionsmentioning
confidence: 99%
“…Исследования проведены на сплаве Ti 49.8 Ni 50.2 (ат.%) производства ООО «Промышленный центр МАТЭК-СПФ», который в состоянии поставки имел структуру моноклинной мартенситной фазы B19'. Последовательность изготовления образцов для исследования описана в работе [4]. Образцы с различной величиной истинной деформации е (1.84; 3.60; 5.40; 7.43; 9.55) получали изотермическим abc-прессованием при 300°С.…”
Section: Doi: 1017223/978-5-907442-03-0-2021-136unclassified